Using chemical genetics and ATP analogues to dissect protein kinase function - Elphick, L; Lee, SE; Gouverneur, V; Mann, D (2007)
Protein kinases catalyze the transfer of the γ-phosphate of ATP to a protein substrate and thereby profoundly alter the properties of the phosphorylated protein. The identification of the substrates of protein kinases has proven to be a very difficult task because of the multitude of structurally related protein kinases present in cells, their apparent redundancy of function, and the lack of absolute specificity of small-molecule inhibitors. Here, we review approaches that utilize chemical genetics to determine the functions and substrates of protein kinases, focusing on the design of ATP analogues and protein kinase binding site mutants. © 2007 by American Chemical Society.